Actual problems of acceptance and delivery of electronic archival documents in the Republic of Kazakhstan (Journal of history-rus, 2024)
The development of electronic resources and digital technologies has contributed to the transition to electronic document management and digitalization of document management. The question arises regarding the high-quality storage and creation of electronic archives. Therefore, the purpose of our article is to study the regulatory legal acts of the state that regulate the activities of the electronic archives of the country. To achieve this goal, the following tasks should be addressed: creating a list of documents included in the country’s electronic archive, examining the rules for digitizing and publishing archival documents in the Republic of Kazakhstan, and identifying current challenges and prospects for developing electronic archives.Results. With the adoption of the "Digital Kazakhstan" program, over 500,000 sheets of archival documents are digitized annually. However, by the beginning of 2023, only 5% of the nearly 16 million storage units in public storage within the National Archival Fund of Kazakhstan have been transferred to electronic format. This indicates low efficiency in using information systems in archives. The study showes that the country's archives carry out the online service «Issuance of archival certificates, copies of archival documents or archival extracts», they are available to citizens through the official website www.egov.kz and the «EGov» mobile application. The availability of digitized archival materials varies significantly in such regional archives of the country as the West Kazakhstan, East Kazakhstan and Aktobe regions; search and access to electronic materials on their official web pages is easy and fast, while the web pages of the archives of Almaty, Pavlodar , Mangistau, Kyzylorda, Karaganda, Zhambyl regions is limited. Conclusions. The study showed that the list of documents included in the electronic archive is not legally defined, the validity period of the electronic digital signature expires within one year, which further raises doubts about the legality of such documents. It is crucial to not only enhance the regulatory framework for archives and documentation but also create guidelines for archives to develop web resources.Key words: electronic archive, Kazakhstan, digitalization, implementation, legal acts.